Use of Extracorporeal Membrane Oxygenation in Refractory Cardiogenic Shock. Issue 1 (January 2016) - Tariq, Sohaib; Gass, Alan
Abstract : Cardiogenic shock is a condition marked by low cardiac output and end-organ hypoperfusion frequently requiring hemodynamic support, and it carries a high mortality. Extracorporeal membrane oxygenation (ECMO) is an effective tool in providing mechanical circulatory support in patients with cardiogenic shock refractory to conventional medical therapies. ECMO can be an essential bridge to recovery, ventricular assist device implantation or transplant. A multidisciplinary team approach is needed in managing such patients and intensive monitoring is required to avoid complications from ECMO. Nevertheless, randomized clinic trials are warranted to prove a survival benefit.